2019
DOI: 10.3390/tropicalmed4030102
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Amongst People with Podoconiosis and Lower Limb Lymphoedema of Other Cause in Cameroon: A Cross-Sectional Study

Abstract: Evidence is emerging that shows elevated mental distress and disorder amongst people with several neglected tropical diseases (NTDs). This study aimed to establish the prevalence of depressive symptoms amongst people with podoconiosis and lower limb lymphoedema of other cause in Cameroon. The study was part of a larger research piece that mapped the geographical distribution of podoconiosis in Cameroon. The Patient Health Questionnaire (PHQ-9; mean) was employed to determine the prevalence of depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“… 37 A study in Cameroon used the PHQ-9 scale to demonstrate a high prevalence of depressive symptoms (38.5%) among individuals with lower limb lymphoedema (predominantly due to podoconiosis), although the majority had mild depression. 38 Studies on individuals affected by leprosy have also reported a high burden of depression. 39 , 40 For example, the prevalence of psychiatric morbidity among leprosy patients in Nigeria was found to be 58% and most cases had depression.…”
Section: Discussionmentioning
confidence: 99%
“… 37 A study in Cameroon used the PHQ-9 scale to demonstrate a high prevalence of depressive symptoms (38.5%) among individuals with lower limb lymphoedema (predominantly due to podoconiosis), although the majority had mild depression. 38 Studies on individuals affected by leprosy have also reported a high burden of depression. 39 , 40 For example, the prevalence of psychiatric morbidity among leprosy patients in Nigeria was found to be 58% and most cases had depression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our previous study in Cameroon, which employed a very similar design to the research reported in this paper, found that 38.6% of people with lower limb lymphoedema displayed at least mild depressive symptoms. 18 Studies in northern Ethiopia with podoconiosis patients 9 and in Nigeria with LF patients 19 reported rates of 12.6% and 20% for depression, respectively. One partial explanation for the higher figures in our Rwandan study may be that rates of depressive symptoms within the general population, even in those without chronic disease, might be higher in Rwanda than elsewhere because a large part of the population who survived the 1994 genocide are still experiencing mental disorders such as depression, panic disorder and post-traumatic stress disorder 27 ; indeed, a recent nationwide mental health survey in Rwanda estimated prevalence rates for depression to be 11.9% in the general population and 35% among genocide survivors, 27 while the aforementioned studies from Ethiopia 9 and Nigeria 19 reported depression rates of 0.7% and 3.1–5.2% among healthy neighbours and the general population, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the second stage, during November and December 2017, the 1143 suspected cases were verified as either podoconiosis (n=914; 80.0%) or lower limb lymphoedema of another cause (n=229; 20.0%) by locally recruited expert clinical diagnostic teams, each of which included four health workers, a medical doctor, a nurse, a laboratory technician and a team leader, using procedures that had previously been employed during a mapping study in Cameroon. 18 , 23 All individuals with suspected podoconiosis were physically examined, and a diagnosis of podoconiosis or lymphoedema of another cause was established through this physical examination, as well as via history and disease-specific tests. A podoconiosis case was defined as a person residing in the surveyed district for at least 10 y who had bilateral, asymmetrical lymphoedema of the lower limb lasting for >1 y, negative Filariasis Test Strip (Alere; Scarborough, ME, USA) and Wb123 tests, and a history of any of the signs and symptoms associated with podoconiosis (for more details on this, including information on the aetiologies of those with lymphoedema of another cause, see the larger mapping study conducted by Deribe et al 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be accompanied by apparent shortening of the toes also performed using a simplified version of the 12-item Self-Reporting World Health Organization Disability Assessment Schedule (WHODAS) 2.0 [14,15]. Additionally, in Cameroon depression is being assessed in patients with podoconiosis [16]. Treatments were randomized prior to the study start and subjects were entered sequentially to receive placebo or doxycycline 200 mg (or if appropriate the lower 100 mg dose) daily for six weeks.…”
mentioning
confidence: 99%